The Influence of Content Marketing, Live Streaming And Free Shipping Programs on Customer Buying Interest in Shopee E-Commerce - Ali Makhmud; Nurul Badriyah; Titin Titin (Jurnal Multidisiplin Sahombu, 2025)
The purpose of the research is to find out the impact of content marketing, live streaming and free shipping programs on customers' buying interest in shopee e-commerce. The research is quantitative. The data collection method is in the form of interviews, questionnaires and observations. The population of this research forgets the students of the Islamic University of Lamongan in 2023. In this study, the sample used was 98 respondents. The results of the study showed that the variables of content marketing, live streaming and free shipping programs had a positive and significant effect partially on the clone milnat belli. The variables of content marketing, live streaming and free shipping programs have a positive impact on the success of the Simlultan Slecara Slable Facing Milnat Belli Klonsumen.